Pharmaceutical services performed in primary health care: a conjunctural analysis of the performance of pharmacists in a municipality in southern Brazil - Carolina Gessinger BERTÓ; Samara Jamile MENDES; Fernanda MANZINI (Revista Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: To identify the pharmaceutical services provided in Primary Health Care (PHC) in a city in southern Brazil and understand the potential and weaknesses in carrying them out, according to the perception of pharmacists. Methods: This is a qualitative study with pharmacists and residents who work in District Reference Pharmacies. Pharmacists completed a questionnaire to help identify pharmaceutical services provided in PHC. A pharmaceutical service was considered performed when the level of agreement was greater than or equal to 70% (Delphi technique). The services that did not reach agreement were selected and discussed in a face-to-face workshop, using a consensus technique (traditional committee). After the workshop, a focus group was held to understand the potential and difficulties in implementing the identified services. Results: Eight managerial technical pharmaceutical services and 26 technical assistance pharmaceutical services were identified, carried out or with the potential to be carried out in PHC services in the city studied. Among the potentialities, the recognition of pharmaceutical services by health teams and the support of local management stand out. Pharmacists pointed out the work overload caused by the great demand for activities and the absence of pharmacy teams and the lack of clinical training of professionals to work in PHC as a complicating factor, especially when carrying out technical pharmaceutical assistance services. Conclusion: The research findings reinforce the need to expand Reference Pharmacies, as well as pharmacists trained to work in PHC.